Doctors and social media – good, bad or both? a Malaysian perspective - Abdul Rashid, Aneesa; Devaraj, Navin Kumar (Consortium of Islamic Medical Colleges, 2020)
Whether we like it or not, social media has become part and parcel of daily living. We use it not only for personal, but also daily use. Social media may offer many benefits for the healthcare professionals, however we also must not ignore the harmful impact it may cause. This article discusses the trending issue of use of social media among doctors.